This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: 1 (sin( t )). Let x 2 ( t ) = x 1 ( t-t ). Note that y 2 ( t ) = x 2 (sin( t )) = x 1 (sin( t )-t ), which is NOT equal to y 1 ( t-t ). 5. Let the input and the output of the inverse system be y [ n ] and z [ n ]. Input-Output Relationship: z [ n ] = y [ n ] – y [ n-1]. D y [ n ] z [ n ] +-1 6. (a) Choose a = b = 1. (b) Choose b = a , and x 2 ( t ) = x 1 ( t ), OR choose b = 0. 7. No. There are many counter-examples. Here is one of them: x 1 ( t ) = sin t and x 2 ( t ) = -sin t . Their sum is equal to zero, thus having zero power. But the power of x 1 ( t ) and x 2 ( t ) are both positive and non-zero....
View Full Document
- Spring '09